Estimation of cervicocephalic kinesthetic perception and its correlation with fall risk in adults with diabetes and without diabetes experiencing cervical pain: A comparative study. - Shilpi Anand; Divya Aggarwal; Sahar Zaidi; Himani Kaushik; Irshad Ahmad; Debjani Mukherjee; Ghada Mohammed Koura; Emadeldin Mohammed Mukhtar; Nasrin Mansuri; Fuzail Ahmad; Ravi Shankar Reddy; Muhammad Sufyan (PLoS ONE)
Aims This study aimed to evaluate the relationship between cervicocephalic kinesthesia sensation and the incidence of falls in adults with Type 2 Diabetes Mellitus (DM-2) experiencing cervical pain. Methods The research was conducted between January 1, 2022, and August 15, 2022. A total of 60 participants were included, with an average age of 26.03 ± 3.45 years and an average BMI of 21.4 ± 2.05 kg/m². Participants were divided into two groups: an experimental group of adults with DM-2 and cervical pain, and a control group without DM-2 but with cervical pain. Results Head repositioning errors were significantly higher in the experimental group for right-side and left-side lateral flexion (P = 0.002). Forward flexion also showed a significant difference between groups (P = 0.006). However, no significant differences were observed between the groups in extension (P = 0.589). No considerable differences were noted in the Berg Balance Scale (BBS) and Neck Disability Index (NDI) scores between the groups. Conclusions Individuals with DM-2 experiencing neck pain exhibited minimal errors in head repositioning tests, yet no substantial alterations were evident in NDI and BBS scores.